Caudal vena cava thrombosis syndrome (CVCT) in a Holstein cow: case report - Córdoba Parra, Juan David (2022)
A case of caudal vena cava thrombosis is reported in an 8-year-old Holstein cow from a herd in Sopo, Cundinamarca, Colombia. The patient presented haemoptysis, epistaxis, cough and ruminal hypomotility. A blood count, blood chemistry, stool analysis and transthoracic ultrasound were performed and a presumptive diagnosis of caudal vena cava thrombosis syndrome (CVCT) was given. The prognosis was bad. The cow remained in hospital for 27 days, dying of acute haemoptysis and suffocation. Necropsy was performed and CCTV confirmed. Hepatic abscesses and septic thromboembolism were evidenced in the portal circulation, in the vena cava and at the pulmonary level, with chronic suppurative pneumonia and an extensive clot at the level of the trachea.